Εκτίμηση Απωλειών Νερού και Διαχείριση Πίεσης σε Δίκτυα Ύδρευσης - Κίγκας, Κωνσταντίνος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών. Τομέας Έργων Υποδομής και Αγροτικής Ανάπτυξης. Εργαστήριο Εγγειοβελτιωτικών Έργων και Διαχείρισης Υδατικών Πόρων, 2017)
The current diploma thesis deals with the losses in water distribution networks, their causes and the factors that affect the quantity and value of water lost. The main objective is to provide guidelines, methods and tools aimed at reducing water losses, particularly through pressure management. Initially, it is shown why the management of urban water supply networks is important. Water is considered a valuable material which is to be protected, while on the other hand in the distribution networks observed large water losses. Furthermore, we describe the typical process design and analysis of water supply systems, the hydraulic relations, the mathematical foundation for the solution of hydraulic networks and their equipment. We analyse the pressure water management and present the concepts of real and apparent water losses. We determine the volume and value of water losses, their lowering reasons and their optimum level. Next, we give a detailed report on the level of water losses and analyze the concepts of minimum night flow rate and minimal night consumption. Without proper knowledge of the losses it is impossible to find proper and efficient reduction solution. The pressure management is considered the most effective way to reduce water losses, since it leads to drastically reduce both leakage and future fracture. Methods and tools reducing the actual losses through pressure management are presented. We analyze pressure modulation scenarios, describe the concepts and types of pressure regulating valves, pressure management areas. For demonstration purposes we plan and design a pressure management system. Finally, using the WB-Easy Calc. software package we calculate the volume and the value of the water loss of a selected municipal water distribution network and make further adjustments aiming at operating pressure reduction to observe the benefits from a pressure management program on the network.